Scaffold-free and scaffold-based cellular strategies and opportunities for cornea tissue engineering. (26th July 2021) - Hussain, Zahid; Pei, Renjun
Abstract: The human cornea is a dome-shaped, multilaminar, transparent, immune-privileged membrane in the front of the eye's optical system. The cornea protects the intraocular parts and letting light into the interior for an image formation on the retina through a crystalline lens. Infection, inflammation, traumatic disorders, and systematic diseases mediate structural changes in the cornea, resulting in irreversible blindness. Up to 12 million patients are awaiting treatment. The inconsistencies in corneal transplantation and artificial implant side effects underscore the need for tissue engineering to address this gap. This study outlines limitations in current corneal treatment and highlights the self-healing potential of each corneal cellular layer to frame necessities for cell-based bioengineering strategies. This study discusses principles, current progress, construct design, and opportunities of scaffold-free and scaffold-based cellular strategies towards repairing epithelium, endothelium, stroma, and full-thickness cornea.